Grid investment and support schemes for renewable electricity generation - Johannes Wagner (Institute of Energy Economics at the University of Cologne (EWI), 2016)
The unbundling of formerly vertically integrated utilities in liberalized electricity markets led to a coordination problem between investments in the regulated electricity grid and investments into new power generation. At the same time investments into new generation capacities based on weather dependent renewable energy sources such as wind and solar energy are increasingly subsidized with different support schemes. Against this backdrop this article analyzes the locational choice of private wind power investors under different support schemes and the implications on grid investments. I find that investors do not choose system optimal locations in feed-in tariff schemes, feed-in premium schemes and subsidy systems with direct capacity payments. Consequently, inefficiencies arise if transmission investment follows wind power investment. A benevolent transmission operator can implement the first-best solution by anticipatory investment behavior, which is however only applicable under perfect regulation. Alternatively a location dependent network charge for wind power producers can directly influence investment decisions and internalize the grid integration costs of wind power generation.
Keywords: D47; D62; L94; Q28; Q48; 330; renewable energy investment; transmission investment; coordination problem; external effects